Strategi Peningkatan Kualitas Sumber Daya Manusia UMKM Melalui Pendampingan oleh Rumah BUMN Kabanjahe - Eikhel Suramana Barus; Frans Antoni Sihite; Diki Febrianto Marbun; Benni Purba (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze strategies for improving the quality of Human Resources (HR) of Micro, Small, and Medium Enterprises (MSMEs) through mentoring programs conducted by Rumah BUMN Kabanjahe. MSMEs play a strategic role in the national economy; however, they still face various challenges, particularly in terms of HR quality, such as limited managerial skills, low financial literacy, inadequate utilization of digital technology, and lack of business innovation. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing and verification. The focus of the study includes the initial condition of MSME HR quality, the forms of mentoring programs provided, and the effectiveness of mentoring in improving the competence and performance of business actors. The results indicate that the mentoring programs include business management training, basic financial management, digital marketing, business legality assistance, and continuous mentoring. These mentoring efforts have proven effective in enhancing knowledge, skills, motivation, and adaptability of MSME actors toward digital transformation. In addition, business performance has improved, as indicated by increased revenue, customer growth, and product quality. Thus, a structured, sustainable, and locally need-based mentoring strategy is a key factor in improving the quality of MSME human resources. This study recommends strengthening collaboration between Rumah BUMN, local government, and educational institutions to create sustainable and competitive MSME HR development.